Biosynthesis of D/L-lactate from methylglyoxal. (19th November 2022) - Zhou, Xiaozhuang; Zhang, Nan; Hossain, Farzana; Kandalai, Shruthi; Tian, Haiyan; Zheng, Qingfei
Abstract: Lactate is a common metabolite generated during anaerobic glycolysis from all three domains of life, which plays significant biological roles in health and disease states, especially cancer development. The most well-established biosynthetic pathway of lactate is the reduction of pyruvate mediated by lactate dehydrogenase (LDH). Here, we report another lactate source – the conversion of methylglyoxal (MGO) by an epigenetic eraser enzyme, DJ-1. In this study, we have uncovered that DJ-1 converts MGO to D- and l -lactate in two different manners. First, as a glyoxalase, DJ-1 stereoselectively transfers MGO to d -lactate in the presence of its cofactor, glutathione (GSH). On the other hand, as a protein deglycase, DJ-1 is able to rescue MGO-modified peptides/proteins (including itself) in the absence of GSH, resulting in the production of both D- and l -lactate. Our discoveries in this work distinguished the glyoxalase and deglycase activities of DJ-1 by tracking the stereochemistry of its product, lactate; thus, this study provides direct chemical evidence to confirm DJ-1 as a bona fide deglycase and new insights into the pathological effects of DJ-1 in carcinogenesis. Graphical abstract: Image 1